COMING OUT SEBAGAI STRATEGI PRESENTASI PEKERJA MINORITAS SEKSUAL MELAWAN DISKRIMINASI MENURUT ONTOLOGI MATEMATIKA ALAIN BADIOU - Syaebani, Muhammad Irfan; Ekosiwi, Embun Kenyowati (Jurnal Filsafat "WISDOM", 2017)
Sexual minority workers often choose to hide their true sexual identity to avoid discriminative action towards them. This leads to their invisible position in the workers presentation. Hiding true sexual identity of sexual minority workers creates exclusive relationship between heteronormative majority workers and non-heteronormative minority workers because of unavailability of intensive and personal interactions between them. Thus it makes sexual minority workers are excluded from the workers presentation and preserving discrimination based on sexuality. Using mathematical theory formulated by Alain Badiou, this writing tries to propose a strategy for sexual minority workers to be visible in the workers presentation through coming out action as an event. Coming out in the end is a strategy to fight for equality and an action for discrimination based on sexuality to end.